(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The transition from academic life to professional employment is a significant milestone for hotel management students, demanding a blend of technical skills and adaptability to industry expectations. This study explores pre-placement perceptions, mindsets and coping strategies of final-year students in the field. Objectives: The study aimed to assess students’ perceptions of the job market, analyse their mindset toward placements and identify coping mechanisms, with a focus on gender differences. Methodology: A descriptive research design with convenience sampling was employed, collecting data through a structured questionnaire using Google Forms from 384 students at NCHMCT-affiliated institutions across India. A structured questionnaire measured perceptions, mindset and stress management strategies. Data analysis utilized SPSS, including descriptive statistics, T-tests and Chi-square tests. Results: Findings reveal that students hold optimistic pre-placement perceptions, with a mean score of 3.83 on a 5-point Likert scale (T = 31.247, p < 0.001), indicating a significant deviation from a neutral outlook. Students with a growth mindset demonstrated significantly higher proactivity scores (Mean: 4.2, SD: 0.8) compared to those with a fixed mindset (Mean: 3.1, SD: 1.1; T = 5.34, p < 0.001). Gender differences were significant in coping strategies, as males relied more on problem-solving approaches while females favoured social support. The most common coping mechanisms included family and peer support, along with self-motivation. Conclusion: The study underscores the importance of mentorship, workshops and gender-sensitive support to prepare students for placements. Recommendations focus on fostering resilience and providing institutional support to enhance career readiness.